Sistem Informasi Eksekutif Pada Sistem Informasi Pengembangan Sumber Daya Manusia Universitas Muhammadiyah Surakarta - Purnomo, Aji Hutomo, Husni Thamrin S.T., M.T., Ph.D (2017)
Informations Systems (IS) help people in accomplishing their job. A form of IS is Executive Information System (EIS). EIS is a computerized system that provides quick acces for executives in searching for important information. EIS can also help executives in identifying and obtaining the important infromation in order to monitor and identify the opportunities and problems. Information system at the Biro Pengembangan Sumber Daya Manusia (BPSDM) in Universitas Muhammadiyah Surakarta (UMS) does not have yet summary features so that it reduces support in decision making. Its existent in decision support is not effective and efficient. the objective of our work is to improve the IS with data summary of lectures and educational staff at UMS. The system is built using Waterfall method that includes several stages such as analysis of the system reuirement. Requirement analysis includes interview processes with deans and the Head of BPSDM in UMS. The system presents data in the form of tables and graphs. System implementation uses Python Framework and MySQL database. The system was tested using black box method. The result from this work is a web based application with summary feature integrated with the existing system. It expectedly facilitates the executive in obtaining summary data of staff at UMS in the form of graph or table with the responsive display.